The Role of Physiological Stress on Victims of Crime in Pakistan: Pathological Insights into Trauma, Injury Healing, and Long-Term Health Effects - Asif Cheema, Aamina; Malik, Noor-un-Nisa; Aftab, Faiza; Naeem, Riffat; Adil, Muhammad; Ishtiaq Gondal, Abdur Rahman (Journal of Neonatal Surgery, 2025)
Background: Crime-related trauma remains a critical public health concern in Pakistan, yet the physiological and pathological consequences of violent crime are understudied. While forensic medicine has traditionally focused on external injuries, limited attention has been given to the interaction between acute stress responses, immune dysfunction, and long-term health outcomes in trauma victims. Objective: To investigate the physiological stress responses, immune alterations, wound-healing patterns, and psychological outcomes among victims of violent crime in Pakistan, and to highlight the need for integrative forensic and psychological care models. Methods: A retrospective analysis of 150 cases of assault, acid attacks, and sexual violence reported to Benazir Bhutto hospital, Rawalpindi between January 2024 and December 2024 was conducted. Data was extracted from medical records, forensic reports, and psychological assessments. Physiological parameters included cortisol levels, heart rate variability, inflammatory markers, and lymphocyte counts measured at baseline, 1 week, and 1 month post-trauma. Wound-healing indicators and psychological outcomes (PTSD symptoms and chronic pain at 6 months) were documented. Statistical analysis was performed using SPSS 24. Results: Victims exhibited a mean 45% elevation in cortisol within 72 hours post-trauma, peaking at 60% in acid attack cases. Elevated sympathetic activity and reduced lymphocyte counts (35% of cases) indicated significant stress-induced immunosuppression. Delayed wound healing was observed in 40% of victims, with markedly elevated CRP levels at 1 week. PTSD symptoms were present in 60% of victims, with persistent symptoms at 6 months in 45%, while 35% reported chronic pain. Secondary infections occurred in 25% of cases, strongly associated with prolonged stress and immune dysfunction. Conclusion: Crime-related trauma in Pakistan triggers significant physiological stress, immune suppression, delayed healing, and high rates of PTSD and chronic pain. These findings underscore the urgent need for multidisciplinary, trauma-informed care integrating forensic medicine, physiological monitoring, and psychological support. Future research should further explore stress–immune interactions in trauma victims and culturally informed rehabilitation strategies.